2020
DOI: 10.1016/j.cognition.2020.104331
|View full text |Cite
|
Sign up to set email alerts
|

Is thirty-two three tens and two ones? The embedded structure of cardinal numbers

Abstract: The acquisition and representation of natural numbers have been a central topic in cognitive science. However, a key question in this topic about how humans acquire the capacity to understand that numbers make 'infinite use of finite means' (or that numbers are generative) has been left unanswered. Here, we test the hypothesis that children's understanding of the syntactic rules for building complex numerals-or numerical syntax-is a crucial foundation for the acquisition of number concepts. In two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Such syntax is in line with the syntactic structures of number words; for example, the phrase structure twenty-seven can be analyzed as [[two -ty] seven] (Hurford, 2007;Guerrero and Park, 2023). Indeed, children's understanding of the structural relationship of multi-digit numbers is dependent on their native languages (Guerrero et al, 2020). Furthermore, Hung et al (2015) reported the neural correlate of syntactically complex multi-digits in the left IFG in a previous fMRI study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such syntax is in line with the syntactic structures of number words; for example, the phrase structure twenty-seven can be analyzed as [[two -ty] seven] (Hurford, 2007;Guerrero and Park, 2023). Indeed, children's understanding of the structural relationship of multi-digit numbers is dependent on their native languages (Guerrero et al, 2020). Furthermore, Hung et al (2015) reported the neural correlate of syntactically complex multi-digits in the left IFG in a previous fMRI study.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the frequent use of mathematical expressions as examples of context-free grammar (CFG;Hopcroft et al, 2006; see Supplementary Information for a CFG-based formal description), theoretical research that adequately describes their syntax in a manner consistent with that of theoretical linguistics remain absent. Although several attempts are made to conduct the theoretical analyses of the natural number system (Watanabe, 2017;Hiraiwa, 2017) and multi-digit numbers (Di Sciullo, 2015;Guerrero et al, 2020;Hurford, 1987Hurford, , 2007, the interpretation of arithmetic expressions and advanced algebraic equations from a linguistic perspective is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that unbounded Merge yields arithmetic is abandoned in Chomsky (2018). An evolutionary argument to this effect is discussed in Casares (2019) [22], and Guerrero et al (2020) [23] brings experimental support from language acquisition. See also Roeper (2022) [24] for discussion.…”
Section: Merge/successor Functionmentioning
confidence: 96%
“…Additionally, Give-N methodology has been expanded with clever variations to test other mathematical cognition theories, such as a Give-N task requesting specific objects ("one person, two animals, and three pieces of furniture") (Sorariutta, Hannula-Sormunen & Silvén, 2017), Give-N tasks with ordinal instead of cardinal responses ("give me the third toy") (Colomé & Noël, 2012;Meyer, Barbiers & Weerman, 2018), Give-N tasks requesting numbers with digits, finger-counting or sets of objects instead of number words (Möhring et al, 2019;Merkley, 2015;Nicoladis, Pika, Marentette, 2010;Salsa & Martí, 2015), a Give-N task prompting place value ("give me twenty-three" with tens and units) (Guerrero et al, 2020) and a Give-N task requesting quantifiers instead of number words ("give me some toys") Sullivan, Bale & Barner, 2018). The Give-N task has proven a versatile research tool beyond just assessment of cardinality acquisition and will likely continue to grow in relevance.…”
Section: Figure 5 Short Checklist To Aid Researchers In the Comprehen...mentioning
confidence: 99%